On Equi-Transmitting Matrices. Issue 2 (October 2016) - Kurasov, Pavel; Ogik, Rao
Abstract : Equi-transmitting scattering matrices are studied. A complete description of such matrices up to order five is given. It is shown that the standard matching conditions matrix is essentially the only equi-transmitting matrix for orders 3 and 5. For orders 4 and 6, there exists other equi-transmitting ones but all such matrices have zero trace.